Paddy farmers' multiple goals and their determinants in the KADA granary area, Malaysia - Mohd Haris, Intan Nurdiah (2010)
The paddy and rice industry in Malaysia is of strategic importance as it provides the main source of food and livelihood for about 206 400 small scale farmers who are generally associated with poverty and low standard of living. Various government programs have been implemented through provision of subsidies;economic activities and transfer of technologies to raise their living standard but their income from farming has not changed significantly. The question is whetherthere is possibility that farmers’ objective in farming differs from the income maximization objective of government programs. In other words, income maximization may not be the main objective of the farming community. This factor has led to the assumption that goals other than profit maximization compete strongly in producer’s decision making. Besides maximizing profit through paddy cultivation, farmers also pursuing other goals such as having more times with the family, to have time for social and religious related activities in order to maximize their utility as a paddy farmer. The main objective of this study is to investigate the farmers’ multiple goals in paddy production. Subsequently, the determinants of these goals are identified. The study was conducted in the region of Kemubu Agricultural Development Authority (KADA) granary area involving 325 respondents. The descriptive analysis was used to describe the characteristics of variables in terms of frequencies and percentage of distribution of the survey. The Simple Ranking Procedure was used to rank the importance of goals by asking farmers to rank nine goals from the most to the least important. In addition, Analytic Hierarchy Process was used to obtain a ratio scale of importance for the nine goals involving the setting up a matrix consisting of observations or judgments based on pair-wise comparisons of the relative importance between and among the goals. Finally, multinomial logistic analysis was used to estimate the effects of independent variables on the selection of the most important goal of farmers. Results from the Simple Ranking Procedure (SRP) and Analytic Hierarchy Process (AHP) show that “Welfare of the Family” and “Have Time For Religious Activities” are the most important goals for farmers in paddy farming activities. This shows that farmers’ preference for being farmer is to maximize utility rather than maximizing profit and income. Result from Multinomial Logistic (MNL) analysis shows that income, age, farm size and experience are having significant influence on the multidimensional goals of paddy farmers in KADA granary area.